Study of Antibodies Expression with Specific Peptide Stimulation Specimens from gp350 / 220 (EBV) in Cell B - Bambang Pristiwanto; Muhaimin Rifa’i (Natural B, Journal of Health and Environmental Sciences, 2013)
Nasopharyngeal Carcinoma (NPC) is caused by Eipstein Barr Virus (EBV) which attack nasopharyngeal epithelium. EBV uses protein gp350/220 in the infection mechanism in nasopharyngeal epithelial surface receptor, CR2. The purpose of this study was to test the vaccine candidate at in vivo method. Mus musculus(Balb/C) mice were used as animal model. In this experiment mice pups in the age of 2 weeks were used. Injection using a specific peptide sequences from EBV showed higher expression of IgM (2.01%) compared to control (1.02%). Injection of this peptide to mice pups also increase the expression of IgM. After injection with this peptide, IgD also increase (75.74) compare to control (65.59%) without manipulation. In contrast, injection of this peptide decreases the expression of IgA antibodies (0.57%) significantly compare to control (1.93%).